The effects of maternal separation stress experienced by parents on male reproductive potential in the next generation - Kajal Khodamoradi; Zahra Khosravizadeh; Hossein Amini-Khoei; Seyed Reza Hosseini; Ahmad Reza Dehpour; Gholamreza Hassanzadeh (Heliyon, 2020)
There is little information available about the effects of early-life parental stress on the reproductive potential of the next generation. The aim of this study is to examine the reproductive potential of male mice whose parents experienced maternal separation stress. In the present study, male first-generation offspring from parents were undergone of maternal separation (MS) were examined. Sperm characteristics, histological changes in testis, reactive oxygen species (ROS) production, expression of apoptotic and inflammatory genes and proteins were assessed. Findings showed that MS experienced by parents significantly decreased the morphology and viability of spermatozoa. Furthermore, significant changes in testicular tissue histology were observed. Increased production of ROS, decreased glutathione peroxidase (GPX) and adenosine triphosphate (ATP) concentrations, and affected the expression of genes and cytokines involved in inflammation. Finally, the mean percentage of caspase-1 and NLRP3 (NOD-, LRR- and pyrin domain-containing protein 3) positive cells was significantly higher in first-generation group. MS experienced by parents may negatively affect the reproduction of first generation offspring.